Deanna Durbin, Judy Garland, and the Golden Age of Hollywood - Gall, Melanie (Guilford, Connecticut : Lyons Press, an imprint of Globe Pequot, the trade division of the Rowman & Littlefield Publishing Group, Inc., 2022)
"The 1930s was a magical age in Hollywood, with Shirley Temple and Mickey Rooney, Bette Davis and Clark Gable lighting up the silver screen. But Deanna Durbin's fame surpassed them all. Born in Canada, Deanna was "discovered" by starmaker Eddie Cantor, producer Joe Pasternak and director Henry Koster, and she quickly became the world's most celebrated star. She saved Universal Studios from ruin, she was a favourite of Winston Churchill and Anne Frank, and she became the highest-paid woman in America. From the start, Deanna's life was irrevocably connected with that of another young ingénue, Judy Garland. Deanna and Judy were wildly talented, ambitious, and strong-willed young women who followed vastly different paths to stardom. While fame was thrust upon Deanna, Judy spent years struggling for success and their early friendship soon turned into a lifelong rivalry. Despite her tragic life, Judy Garland is remembered as an entertainment icon, beloved by millions. However, Deanna Durbin-who turned her back on Hollywood at the age of twenty-eight to pursue love and happiness-has been largely forgotten. But Deanna's legacy endures, and this first-ever biography tells of how her gorgeous voice and winning charm vaulted her to worldwide fame and how a thirteen-year-old girl transformed moviemaking and influenced a generation of fans as the first teenage superstar"--.
Prologue: "Winnipeg's sweetheart" -- Early life -- From MGM to Universal (1935-1936) -- Two smart men -- Three smart girls -- Jenny Lind in Short socks (1937) -- One hundred men and a girl (1937) -- Durbin-Daffy (1937) -- Prints at the Chinese Theatre (1938) -- Deanna Durbin devotees (1938) -- Academy Award (1939) -- The kiss (1939) -- A dash of sophistication (1940) -- The greatest love story (1941) -- Greetings from Mussolini -- Camp tour (1942) -- Deanna in WWII -- War-themed movies (1943) -- The "nightclub singer" -- Two new mothers (1945) -- Highest-paid woman in America (1947) -- Perhaps -- Happily ever after -- Six decades of obscurity.
new book 2022 fall.
Includes bibliographical references and index.
Keywords: Durbin, Deanna; Garland, Judy; Motion picture actors and actresses -- Biography -- Canada; Motion picture actors and actresses -- United States -- Biography; Women singers -- Canada -- Biography; Women singers -- United States -- Biography; Women singers in motion pictures; Musical films -- United States -- History and criticism; Motion pictures -- United States -- History -- 20th century